Factors related to the development of dressing and undressing skills in preschool children - Tantoco, Melita O.
Seventy-eight randomly selected subjects, with ages ranging from 2.5 to 6.6 years, from UP Child Development Center were evaluated on a number of dressing and undressing tasks. Data obtained were subjected to Reed Muench and Probit analysis to determine the age of attainment of each of the dressing and undressing tasks at the 60th percentile rank. It was found out that 75% of the dressing and undressing skills were developed by the age of 42 months; that undressing skills could be performed earlier than the dressing skills and hat such tasks requiring fine finger movements were the last to be attained. The performance scores were analyzed for correlation with the following variables: sex, birth order, primary caretaker, number of children in the family and number of "significant other" through the use of Contingency Coefficient of C. It was found out that the degree of dressing and undressing skills was significantly correlated with sex in age groups 2 - 3 and 2 - 6 years and with the number of children in the family in age groups 5 and 2 - 3 years. The development of dressing and undressing skills was also found to be correlated at a highly significant level 2 - 6 years.